Learning c for arduino - Syed omar faruk towaha (UK : Packt publishing ltd, 2017)
This book will start with the fundamentals of C programming and programming topics, such data types, functions, decision making, program loops, pointers, and structures, with the help of an Arduino board. Then you will get acquainted with Arduino interactions with sensors, LEDs, and autonomous systems and setting up the Arduino environment. Includes index
Keywords: Computer program language